Estimasi Waktu Berakhirnya Gempa Susulan Menggunakan Model Peluruhan Statistik: Studi Kasus Gempa Bumi Bawean 22 Maret 2024 - Martha Rajagukguk; Rayhan Irfan Hielmy (Yayasan Kita Menulis - JoCPES, 2025)
An earthquake struck Bawean Island on March 22, 2024 with a magnitude of 6.5 followed by a series of aftershocks. In this study, the decay of aftershocks in the Bawean region was analyzed from March 22 to March 31, 2024 using the Omori Method, Mogi I Method, Mogi II Method, and Utsu Method. The purpose of this research is to determine the duration of aftershock decay in Bawean and to identify the most suitable statistical method for predicting aftershock decay time in the region. The analyzed data were obtained from the BMKG earthquake repository. By applying the four methods, results were obtained in the form of aftershock decay duration and correlation coefficients for each method. The analysis shows that the most appropriate statistical methods for calculating aftershock decay time in Bawean are the Mogi I Method and the Utsu Method both producing a correlation coefficient of approximately -0.806 and an aftershock decay duration of 24 days consistent with the BMKG earthquake catalog data.